(untitled) (Annals of Medical Research, 2021)
Aim: The cardiovascular system is susceptible to thyroid hormones. Many studies show that hypothyroidism is associated with increased cardiovascular risk, functional abnormalities, atherosclerosis, and increased arterial stiffness. Pulse wave velocity (PWV) and augmentation index (AI) are regarded as indexes of arterial stiffness. Oxidative free radicals that occur during ischemic events cause certain chemical changes in the albumin molecules. The ischemia-modified albumin (IMA) has been suggested as an indicator of oxidative stress. Evaluation of oxidative stress markers and parameters of arterial stiffness can shed light on the mechanism of increased cardiovascular risk in patients with hypothyroidism. Material and Methods: For this study, PWV, AI measurements, and IMA levels of 20 untreated patients with overt hypothyroidism (OH), 21 untreated patients with subclinical hypothyroidism (SH), and 30 healthy controls (control-CNT) were evaluated. Patients and the healthy controls’ gender, age, weight, height, body mass index, waist circumference, smoking habit and blood biochemical results were recorded. Results: PWV was found to be increased in patients with overt hypothyroidism; however, there was no difference in between subclinical hypothyroidism and control group(p=0,881). Also, PWV had a significant positive correlation with; age, BMI, waist circumference, blood glucose, uric acid, pulse pressure and systolic and diastolic blood pressures. IMA levels were not different in between the groups. Conclusion: Hence the increased CV risk in patients with hypothyroidism is a multifactorial state; the interplay of many factors determines it. Future studies with larger sample sizes are needed to evaluate the possible relationship among IMA levels, arterial stiffness parameters and cardiovascular risk factors in patients with hypothyroidism.Keywords: Ischemia Modified Albumin; Arterial Stiffness; Hypothyroidism.